Exclusive Breastfeeding Determinants of Non-working Mothers - Katarina Maria Tjung; Intje Picauly; Rut Rosina Riwu (Lontar : Journal of Community Health, 2020)
The nutritional status in the first 1000 days of life is very important. WHO and UNICEF recommend that newborn babies should only be breastfed for at least six months, so that babies can grow and develop optimally. The recommendation has been applied, but the failure of exclusive breastfeeding still occurs. This study aimed to analyze the determinants of exclusive breastfeeding of not working mothers in the work area of Oesapa Public Health Center, Kelapa Lima subdistrict in 2019. This is a quantitative study with cross-sectional study design. This research was conducted in the work area of Oesapa Public Health Center with a sample of 61 babies. Data analysis used the Chi-Square test and multiple logistic regression tests. The results showed that the variables of mother’s knowledge (ρ= 0,001), mother’s trust (ρ= 0,024), family’s support (ρ= 0,000), and health care provider’s support (ρ= 0,028) are related to exclusive breastfeeding, but mothers’ age (ρ= 0.257) and information exposure (ρ= 1,000) are not related to exclusive breastfeeding. The factor of family’s support (ρ= 0,001) and mother’s knowledge (ρ= 0,005) had the highest correlation with exclusive breastfeeding. The mothers' level of knowledge also had a major contribution to the success of exclusive breastfeeding. To achieve exclusive breastfeeding success, mothers need support from the family (especially husband) and complete information from health workers so the mothers’ knowledge can be improved. The health centers need to utilize various health promotion media to increase the coverage of exclusive breastfeeding.